PELATIHAN IMPLEMENTASI VIRTUAL LAN (VLAN) PADA JARINGAN KOMPUTER DI SMKS PARULIAN 1, KECAMATAN MEDAN KOTA, KOTA MEDAN, PROVINSI SUMATERA UTARA - Daniel H. S. Napitu; Angelia Maharani Purba; Eva M. Simatupang; Arlina Pratiwi Purba; Ernie S. Y. Sitanggang; Susaidin Susaidin (ASOSIASI IDEBAHASA KEPRI, 2026)
The rapid development of information technology demands that educational institutions, particularly Sekolah Menengah Kejuruan (SMK) majoring in Computer and Network Engineering, be able to follow and implement the latest network technologies. One of the basic technologies that must be mastered is the Virtual Local Area Network (VLAN), which allows logical network segmentation to improve efficiency, security, and network management. However, based on initial observations and communication with partners, it was discovered that some schools still do not have adequate module kits to support network management, thus students do not yet have these competencies. This Community Service activity aims to improve the competence of 11th grade students in understanding and implementing VLANs on computer networks. The method used is hands-on lab-based training that includes VLAN configuration using managed switch network devices. From the results of this community service activity, students can understand Virtual Local Area Networks, students' opportunities to do direct practice are more evenly distributed along with the increase in practice modules and increase students' enthusiasm in directly implementing VLANs on computer networks. Keywords- Virtual LAN (VLAN), jaringan komputer, SMK